NILAI-NILAI AJARAN ISLAM KESULTANAN BUTON - La Ode Muhammad Syahartijan; la Ode Jumaidin (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
This research aims at describing the values which are developed in Sultanate of Buton through the concept of Martabat Tujuh in seven level of implementation or seven positions. This research is also aimed to describe the supporting factors on Islam educational value in Sultanate of Buton in the 19th century. The method of this research is a historical method with using Qualitative approach. Techniques of data collection in this research are an interview, library research, and observation. The results show that Islam value in Sultanate of Buton in the 19th century, through the concept of Martabat Tujuh, was well isolating in Sultanate of Buton. Especially Kaomu and Walaka which is taught by the government (Sultan). Religious school, Islamic School, zawiyah, the libraries thrive, implying on the obedience of Butonese society to the teachings of their religion which are shown by the people and leaders (Sultan) as a unity that can not be separated in the system of government in the Sultanate of Buton until the 19th century. Keywords: value, Islamic education, sultanate, Buton